Specifics, character and basic approaches to the treatment of complications of BCG vaccination - N. A. Matsehora; L. P. Omelian; M. G. Melnychenko; V. A. Gudz (Kazimierz Wielki University, 2018)
Introduction. One of the main components of the tuberculosis control program for children worldwide, as well as in Ukraine, BCG vaccination. It is proved that high-quality immunization reduces the incidence of tuberculosis by 7-10 times, and infectivity - by 1.5-3 times. However, the introduction of a vaccine, which is a strain of attenuated live mycobacterium tuberculosis, can lead to the development of complications. The purpose and tasks of the study. To study the prevalence, nature of the course and basic approaches to treatment of surgical complications of anti-TB immunization. Materials and methods. A comprehensive analysis of scientific data on the development of complications of BCG vaccination and own clinical observations has been carried out. Results and discussion. The third part of all the complications is due to the properties of the vaccines themselves, 30-40% of the violations of the vaccination technology and about 30% of the immunological protection of vaccinated children. Among children, boys were predominant: 69 (62.7%), girls 41 (37.3%). BCG complications often occur in the background of anemia (22,3%) and non-specific inflammatory diseases (4,5%). Conclusions. The volume of surgical intervention in BCG-lymphadenitis is determined depending on the stage, nature and severity of inflammatory changes in the lymph nodes.